Thelma & Louise: Rape culture, mudflaps and vaginal horizons - Dayna McLeod (Revista Teknokultura, 2024)
This video essay isolates the rage of the protagonists of Ridley Scott’s 1991 film Thelma and Louise, against personal and systemic patriarchal violence. Using animation, multiscreen, and supercut editing, this video essay supposes what happens when supporting male characters are removed, erased, or diminished to focus our attention on Thelma and Louise’s response(s) to their violent acts. It also imagines mudflap girls –now women– talking and fighting back against their oppressor. Finally, this video essay transforms Thelma and Louise’s suicidal leap into a deep dive of the vagina, often essentialized, in heteropatriarchal discourses, as synonymous with the female body.